Identify the Principles of Perawi Hadith and Journalist Ethics - Datuk Imam Marzuki (Budapest International Research and Critics Institute (BIRCI-Journal): Humanities and Social Sciences, 2020)
This research focus on the equality of the principles owned by perawihadist by typing a reporter is a requirement to be a journalist with integrity. Method library research, using representation theory and hermeneutics. Research results show there is similarities between principles the woman with journals while a journalist, fair, honest and open. Thus also a criterion that must be owned by a reporter according to journalist code.